SINERGITAS TANGGUNGJAWAB PENDIDIKAN PADA TRI PUSAT PENDIDIKAN DALAM MENANGGULANGI KENAKALAN REMAJA DI ERA GLOBALISASI - Zaenuri Zaenuri (Almarhalah | Jurnal Pendidikan Islam, 2021)
ABSTRACKThe responsibility of education cannot be carried out unilaterally, it requires the cooperation of three components which Ki Hajar Dewantara calls the tricenter of education: family, educational institutions, and society. All three are a unified whole and complement each other. The involvement and role of parents and the community in guarding children's education in the era of globalization is very urgent.This journal aims to discuss the importance of the Three Education Centers as a solution to overcome juvenile delinquency which is increasing in this era of globalization. The writing of this journal uses library research methods, or often also called library research, collecting data from various literatures.The three educational centers both play an important role in the success of education, which basically all are interrelated and mutually cooperate with each other. The three of them must indirectly carry out close guidance in the educational process. The three links can be seen from: Parents carry out their obligations to educate children in the family, educational institutions facilitate teaching various knowledge and skills with full support from students' parents, and the community is expected to be a facilitator for students to be able to actualize their knowledge and skills.Â Keywords: Responsibility, Tricenter of Education, Juvenile delinquency, Puberty.